Pharmacokinetics and milk secretion of gabapentin and meloxicam co-administered orally in Holstein-Friesian cows - Malreddy, Pradeep R.; Coetzee, Johann F.; KuKanich, Butch; Gehring, Ronette (My University, 2013)
Management of neuropathic pain in dairy cattle could be achieved by combination therapy of gabapentin, a GABA analog and meloxicam, an NSAID. This study was designed to determine specifically the depletion of these drugs into milk. Six animals received meloxicam at 1 mg/kg and gabapentin at 10 mg/kg, while another group (n = 6) received meloxicam at 1 mg/kg and gabapentin at 20 mg/kg. Plasma and milk drug concentrations were determined over 7 days postadministration by HPLC/MS followed by noncompartmental pharmacokinetic analyses. The mean (±SD) plasma C[subscript max] and T[subscript max] for meloxicam (2.89 ± 0.48 μg/mL and 11.33 ± 4.12 hours) were not much different from gabapentin at 10 mg/kg (2.87 ± 0.2 μg/mL and 8 hours). The mean (±SD) milk C[subscript max] for meloxicam (0.41 ± 0.16 μg/mL) were comparable to gabapentin at 10 mg/kg (0.63 ± 0.13 μg/mL and 12 ± 6.69 hours). The mean plasma and milk C[subscript max] for gabapentin at 20 mg/kg P.O. were almost double the values at 10 mg/kg. The mean (±SD) milk to plasma ratio for meloxicam (0.14 ± 0.04) was lower than for gabapentin (0.23 ± 0.06). The results of this study suggest that milk from treated cows will have low drug residue concentration soon after plasma drug concentrations have fallen below effective levels.
Keywords: Gabapentin; Meloxicam; Milk; Non-compartmental; Dairy cattle; MRL